On L2-Boundedness of h-Pseudodifferential Operators - Jie Yang (Journal of Function Spaces)
Let Tah be the h-pseudodifferential operators with symbol a. When a∈Sρ,1m and m=nρ−1/2, it is well known that Tah is not always bounded in L2ℝn. In this paper, under the condition ax,ξ∈L∞Sρnρ−1/2ω, we show that Tah is bounded on L2.